2012
DOI: 10.1021/cb3003368
|View full text |Cite
|
Sign up to set email alerts
|

Reawakening Atlas: Chemical Approaches To Repair or Replace Dysfunctional Musculature

Abstract: Muscle diseases are major health concerns. For example, ischemic heart disease is the third most common cause of death. Cell therapy is an attractive approach for treating muscle diseases, although this is hampered by the need to generate large numbers of functional muscle cells. Small molecules have become established as attractive tools for modulating cell behavior and, in this review, we discuss the recent, rapid research advances made in the development of small molecule methods to facilitate the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 178 publications
0
18
0
1
Order By: Relevance
“…Similarly, mice treated with the small molecule 2-acetyl-4(5)-tetrahydroxybutlimidazole (THI), previously shown to increase S1P expression, had a 4-fold increase in the number of cells expressing myf5, a protein that plays a key role in regulating myogenesis and a 3.6-fold increase in the number of muscle cell fibers [168]. Another interesting approach that has been explored is using small molecules to dedifferentiate multinucleated myoblasts into mononuclear proliferatory cells and satellite cells which can then contribute to the regeneration at a different site [169,170]. The use of small molecule therapy for skeletal muscle regeneration has been recently reviewed [171].…”
Section: Materials For Cell and Drug Delivery To Aid In Skeletal Mmentioning
confidence: 99%
“…Similarly, mice treated with the small molecule 2-acetyl-4(5)-tetrahydroxybutlimidazole (THI), previously shown to increase S1P expression, had a 4-fold increase in the number of cells expressing myf5, a protein that plays a key role in regulating myogenesis and a 3.6-fold increase in the number of muscle cell fibers [168]. Another interesting approach that has been explored is using small molecules to dedifferentiate multinucleated myoblasts into mononuclear proliferatory cells and satellite cells which can then contribute to the regeneration at a different site [169,170]. The use of small molecule therapy for skeletal muscle regeneration has been recently reviewed [171].…”
Section: Materials For Cell and Drug Delivery To Aid In Skeletal Mmentioning
confidence: 99%
“…Although muscles typically regenerate themselves, the regenerative property can become compromised as people age, if they suffer from a muscular degenerative disease (29), or if they experience a large, traumatic injury, in which the natural repair mechanism is unable to cope with the large muscle loss (30). Small molecules can offer an attractive option to satisfy the clinical need for muscle recovery therapeutics (10, 31).…”
Section: Small Molecule Mediated Skeletal Muscle Regenerationmentioning
confidence: 99%
“…Interestingly, various groups have demonstrated that the dedifferentiation of myoblasts can be beneficial to muscular regeneration. Under certain conditions, multinucleated myoblasts can dedifferentiate into mononuclear proliferatory cells, satellite cells, which then have potential to differentiate into multinucleated cells at another site (29). Recently, Kim et al .…”
Section: Small Molecule Mediated Skeletal Muscle Regenerationmentioning
confidence: 99%
“…[53] [13d, 47,48] Es ist noch viel Arbeit erforderlich, um aufbauend auf diesen Studien Verbindungen -und letztlich klinische Kandidaten -zu identifizieren, die spätere Stadien der Kardiomyozytendifferenzierung adressieren und zu therapeutisch relevanten Kardiomyozytenpopulationen sowie letzten Endes zu einer verbesserten Herzfunktion führen. [54] 2.2. Mikro-RNAs und Anti-Mikro-RNA-Oligonukleotide Mikro-RNAs (miRs) sind kurze (ca.…”
Section: A T Plowright Et Alunclassified